1993
DOI: 10.1042/cs0840537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin-Dependent Diabetes Mellitus on Lipids and Lipoproteins: A Study of Identical Twins

Abstract: 1. Forty-five identical twin pairs, discordant for insulin-dependent diabetes mellitus, were studied with respect to their serum lipid (high-density lipoprotein, low-density lipoprotein, total cholesterol and triacyl-glycerol) and apoprotein [apoprotein A-I, apoprotein B and lipoprotein (a)] concentrations and apoprotein (a) phenotypes. The twins were compared with an age- and sex-matched non-diabetic control group. 2. A significantly higher value was found only for high-density lipoprotein cholesterol in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Serum Lp(a) levels in patients with (n = 11) and without (n= 15) nephropathy were 42.5 +29.5 mg/dl and 62.2+42.8 mg/dl, respectively. This difference was not significant, Dubrey et al [36] reported that albumin secretion does not affect serum apo(a) levels in IDDM. We previously reported a similar finding in NIDDM [13].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Serum Lp(a) levels in patients with (n = 11) and without (n= 15) nephropathy were 42.5 +29.5 mg/dl and 62.2+42.8 mg/dl, respectively. This difference was not significant, Dubrey et al [36] reported that albumin secretion does not affect serum apo(a) levels in IDDM. We previously reported a similar finding in NIDDM [13].…”
Section: Discussionmentioning
confidence: 79%
“…We have previously reported [13] that the Lp(a) concentration was negatively correlated with the apo(a) molecular weight. Dubrey et al [36] studied the effect of IDDM on serum lipid and lipoprotein levels in identical twins and found that IDDM per se has no influence on serum Lp(a) levels, although the correlation within each twin pair was significant. Subjects with the same apo(a) phenotypes within a family show similar plasma Lp(a) levels [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Serum and urinary creatinine were measured on a BM/Hitachi 717 automatic analyzer (Boehringer Mannheim, Lewes, U.K.). Serum total cholesterol and high-density and low-density cholesterol fractions as well as triglyceride concentrations were estimated, as described previously (15).…”
Section: Biochemical Analysesmentioning
confidence: 99%